Singleto Multi Clouds for Security in Cloud Computing by using Secret Key Sharing (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Now a day Cloud Computing is rapidly using computing technology. For low cost and high-end benefits this cloud computing is utilized. The major issue in this cloud computing is Ensuring the security, because the often store sensitive data with third party cloudproviders but these providers may beuntrusted.Working with single cloud is prevented, because in customer’s perception the failure in service availability and thepossibility of viciousgang in single cloud. To overcome these types of failures, a recent and popular technology is emerged called cloud of clouds or multi clouds or inters clouds. In this paper we illustrated the recent research towards multi clouds from single cloud and addressed possible solutions in security concern.Here we used the SSS (Secret Key Sharing) technique to share the key between servers. From this we can found that there is less attention in the field of multi cloud security compare with single cloud providers. The main intention of this work is to reduce the security risks related to cloud users and to encourage theuse of cloud- of -clouds due to its ability.